2005
DOI: 10.1080/08927010500133584
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the upper temperature tolerances of three mussel species in a brackish water canal: Size, season and laboratory protocols

Abstract: Mussels are the most problematic organisms encountered in the water intake systems of electrical power plants. Various fouling control measures are adopted, among which heat treatment is considered the relatively more attractive from economic and ecological points of view. Thermal tolerance experiments were carried out to determine the effects of mussel size (2-20 mm shell length), season (breeding vs non-breeding), nutritional status (fed vs non-fed), acclimation temperature (5-25 degrees C) and acclimation s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 19 publications
(36 reference statements)
1
20
0
Order By: Relevance
“…However, acclimation capacity varies with several factors such as physiological condition and season (e.g. Wilson and Elkain, 1991;Cuculescu et al, 1998;Rajagopal et al, 2005;Healy and Schulte, 2012). Furthermore, experiments evaluating the capacity to acclimate rarely measure the highest temperature that organisms are capable of achieving through acclimation.…”
Section: Warming Allowances and Estimations Of Thermal Resiliencementioning
confidence: 99%
“…However, acclimation capacity varies with several factors such as physiological condition and season (e.g. Wilson and Elkain, 1991;Cuculescu et al, 1998;Rajagopal et al, 2005;Healy and Schulte, 2012). Furthermore, experiments evaluating the capacity to acclimate rarely measure the highest temperature that organisms are capable of achieving through acclimation.…”
Section: Warming Allowances and Estimations Of Thermal Resiliencementioning
confidence: 99%
“…In a subsequent report, Rajagopal et al (2005b) compared their findings on upper temperature tolerances of M. leucophaeata with those of freshwater D. polymorpha and the marine blue mussel Mytilus edulis. Their results for M. leucophaeata in relation to acclimation temperature, acclimation salinity, animal size, breeding season, and nutritional status demonstrated generally similar patterns to those reported by Rajagopal et al (2005a).…”
Section: Oyster Bedsmentioning
confidence: 95%
“…In Europe, where the species is invasive, Vorstman (1933) found specimens at Oosterdock, Amsterdam in salinities from *6 to *10.5; Schütz (1969) reported them from Dutch environments with 3-9 salinity; Van der Velde et al (1992) collected them in the Noordzeekanaal in salinities ranging from 3 to 8; and Rajagopal et al (2005b) reported the species to be common between 1 and 15 salinity in this same canal. Oliver et al (1998) found specimens at Cardiff Docks, South Wales in 15 salinity.…”
Section: Habitat Characteristicsmentioning
confidence: 96%
See 2 more Smart Citations